Topological Optimum Approach for Improving Indicators for Agricultural Sustainability - Waseem Asghar Khan (Journal of Chemistry)
Background. The goal of this study is to improve the topological efficiency of agricultural production in Saudi Arabia’s allocated agriculture area. Method. The data envelopment analysis (DEA) topology was adopted to efficiently identify agricultural land utilization from 2009 to 2013. Results. According to the constant return to scale (CRS) topology, the area may be reduced by 8.7831667 percent in 2009, resulting in a given optimal crop yield scenario. Similarly, the area may be reduced by 3.9425506 percent in 2010 to attain a given optimum crop production topology, by 4.0198591 percent in 2011 to achieve the same amount of crop production, and by 1.0621519 percent in 2012 to attain the desired level of crop output. The topology of crop production could increase by 5.1334182 percent while retaining quality, according to the variable return to scale (VRS) topology while maintaining the same assigned area. Conclusion. Also using the linear programming approach to reproduce the results of CRS and VRS models.